7,071 UMP students back on campus - Siti Nur Azwin, Zulkapri (2022)
PEKAN, 7 March 2022 – A total of 7,071 Universiti Malaysia Pahang (UMP) students are returning to both the Pekan and Gambang campuses starting on 4 March in stages for physical academic activities for Semester II Academic Session 2021/2022.